IMPLEMENTASI PENDEKATAN SAINTIFIK DAN KECAKAPAN ABAD 21 DALAM RENCANA PELAKSANAAN PEMBELAJARAN - Talitha, Stella; Mahajani, Tri; Nurjaman, Aam; Hilal Mukhtar, Ruyatul (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
The pedagogical competence is the teacher's ability with regard to understanding of learners and the management of the debriefing from planning, executing to evaluating. This competence consists of the ability to develop a curriculum related to a capable subject. The problem identified is (1) a knowledge of the components in curriculum 2013's RPP; (2) the teacher's understanding of the saintifical approach and the scientific learning models; And (3) teachers' inadequate ability to create an RPP based curriculum 2013. The purpose of this PKM is increased development of RPP based on application of a saintifical approach based on curriculum 2013. The method in this PkM, first establishing the target area and applying the appropriate permits for carrying out the activity to authorized institutions. Second, coordinating with the head of SMP Binagreha Bogor and preparing training materials, the implementation of PPK, literacy, 4C, HOTS, scientific approaches, and scientific learning models. Third, training at SMP Binagreha Bogor. In the training, methods the team uses are methods of lectures, demonstrations, discussions, and tasks. The result of PkM in collaboration with SMP Binagreha Bogor in general is increased development of RPP based on application of a saintifical approach based on curriculum 2013. Specific targets that have been achieved in this activity is the increasing knowledge of PPK implementation, literacy, 4C, HOTS, scientific approaches, and scientific learning models in RPP